Reconstitution of muscle F‐actin from Atlantic salmon (Salmo salar L.) with carotenoids—binding characteristics of astaxanthin and canthaxanthin. (24th February 2017) - Young, A.J.; Pritchard, J.; Lowe, G.M.; Crampton, V.; Buttle, L.
Abstract: The binding of carotenoids to the myofibrillar protein F‐actin purified from the white muscle of Atlantic salmon ( Salmo salar L.) was studied using in vitro reconstitution. The binding of astaxanthin and canthaxanthin was saturable, and analysis revealed the presence of a single carotenoid‐binding site. The dissociation constants (Kd ) for actin prepared from 2.5 kg FW (Fresh Weight) fish were 1.04 ± 0.13 μg carotenoid per milligram of actin and 0.54 ± 0.11 μg/mg for astaxanthin and canthaxanthin, respectively. The saturation binding level (Bmax ) for astaxanthin was 1.39 ± 0.07 μg/mg and 1.04 ± 0.08 μg/mg for canthaxanthin. These values were higher for F‐actin prepared from organic and small ( 0.5 kg FW) salmon than for non‐organic and larger, mature fish. The structural specificity of carotenoid binding revealed a preference for carotenoids that possess a keto group at C‐4 on the β end group of the molecule, but the presence of hydroxyl groups at C‐3 or C‐4 reduced overall binding efficiency. The study suggests that the ability of myofibrillar proteins to bind carotenoids is not a limiting factor governing the deposition of carotenoids in the muscle of salmonids.